A test for Io's magma ocean: Modeling tidal dissipation with a partially molten mantle. Issue 11 (3rd November 2016) - Bierson, C. J.; Nimmo, F.
Abstract: Magnetic induction measurements and astrometry provide constraints on the internal structure of Io, a volcanically active moon of Jupiter. We model the tidal response of a partially molten Io using an Andrade rheology which is supported by silicate deformation experiments. This model uses material properties similar to the Earth's mantle and includes feedbacks between partial melting, tidal heat production, and melt transport. We are able to satisfy constraints provided by the measured imaginary part of the tidal Love number I m ( k 2 ), the inferred depth and melt fraction of a near‐surface partially molten layer, and the observed equatorial concentration of volcanic landforms. We predict a value for the real part of the tidal Love number of R e ( k 2 ) = 0.09 ± 0.02, much smaller than the value of R e ( k 2 )≈0.5 predicted for an Io with a fluid magma ocean. Future spacecraft observations should be able to measure this value and test which model is correct. Key Points: We self‐consistently model dissipation and melt production in the interior of Io If Io has a partially molten magma reservoir, as opposed to a magma ocean, that reservoir must be greater than 100 km thick We make a prediction of the tidal Love number k 2 . This value can be measured by spacecraft and used to determine if Io has a magma ocean